Performance analysis of packets scheduling with preemptive: article / Norjanah Kastaman - Kastaman, Norjanah (2003)
This paper presents a performance analysis of packets scheduling with preemptive in three commonly used scheduling mechanisms: WFQ, First in First Out and Priority Queuing. We implement a scheduler model and incorporate it into the IP layer output queues using OPNET 10.5 simulation tool. We measure the performance of the algorithms in terms of delay time, size of packet and overflow from different traffic flows during various time periods. We also simulate a network running several Internet applications: VoIP, FTP, video conferencing. Our simulation results indicate comparison of Priority Queuing, WFQ and First in First Out in internet application